Muscle rigidity, sensory disorder and antipsychotics: A case report - Ramos-Cabrera, Víctor (2019)
In emergency rooms with large numbers of assigned population, we often see isolated conditions, such as severe dehydration, hypernatremia or hyponatremia, acute kidney injury, sensory disorder, among others. However, many of these conditions are part of a single disease and, if they are not gathered together as a medical unit at the right time, morbidity and mortality may drastically increase, especially in the event of diseases with a very rare or unusual frequency. Such is the case of the following disorder, which could worsen the critical condition of the patient if it is not detected on time or not treated appropriately. This clinical case addresses a 74-year-old female patient who reports a history of psychotic disorder with irregular treatment and, after the intake of carbamazepine and risperidone, presents the typical and infrequent symptoms of neuroleptic malignant syndrome (NMS).